(untitled) (Baltic Journal of Sport and Health Sciences, 2011)
Research background. Stretching is believed to enhance performance, reduce injury, and be an effective means of developing flexibility and alleviating muscular soreness (Shellock, Prentice, 1985; Brandy et al., 1997). A review of the current literature shows that the results of many studies conflict with others; some report that static stretching diminishes vertical jum (VJ) performance (Cornwell et al., 2001; McNeal, Sands, 2003; Wallmann et al., 2005), whereas others report that static stretching has no effect at all on VJ (Church et al., 2001; Power et al., 2004; Unick et al., 2005). Research aim, was to examine the effects of different durations of stretching on performance and to find the stretching durations that affect the performance negatively or positively. Research methods. The subjects of the study were 27 rhythmic gymnasts with the mean age of 10.00 ± 1.2 years. The subjects as a whole group participated in two different stretching programs on nonconsecutive days to eliminate the effect of individual differences on the performance. On the first day, athletes were asked to warm up by 5 minute jogging after the pretest was administered. The posttest measured the vertical jump performance after athletes stayed inactive for 20 minutes. They rested for a day and on the third day, their performance was measured again. After the 5 minute warm-up period, 10 repetitions of 15 seconds static stretching exercises for hip flexor, hamstring and gastrocnemius muscle groups were followed by the posttest. Moreover, on the fifth day 30-second exercises were repeated five times on the same type of muscles. The participants in this investigation were tested in individual vertical jump performances following warm-up only, warm-up plus 15 seconds static stretching, and warm-up plus 30 seconds. Research results. Results of a one-way repeated-measures ANOVA indicated a nonsignificant difference for vertical jump performance (F = 2.052; p > 0.05). Discussion and conclusions. Stretching exercises are referred in rhythmic gymnastics more intensively than other sports. Relevant literature displays fewer stretching repetitions and durations. These durations and repetitions may not be realistic and practical for rhythmic gymnasts. Therefore, the durations and repetitions utilized in this study are considered more appropriate for rhythmic gymnastics trainings. Rhythmic gymnasts may make use of duration and repetitions determined in this study that will not affect their performance. Keywords: anaerobic power, gymnastics, exercise.